SOCIAL INTERPRETATION OF “WAJAH OTT” IN POLITICAL COMMUNICATION MANAGEMENT CONTEXT OF PAUL RICOUER ANALYSIS (HAND CATCH OPERATION KPK -“OTT’S FACE”) (Economic and Bussiness Faculty, Dr Soetomo University, 2018)
The writing purpose to understand and criticize Social Text